Peran Guru Pendidikan Pancasila Dalam Meningkatkan Minat Belajar Siswa Menggunakan Aplikasi Canva di SMAN 1 Pulau Laut Kepulauan - Yaisah Yaisah; Muhammad Elmy (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to provide an in-depth description of the planning and implementation of learning, as well as increasing student interest in learning through the use of the Canva application as a digital learning medium. This type of research is descriptive with a qualitative approach. Data collection techniques were carried out through observation, in-depth interviews, and documentation involving the Principal, Pancasila Education teachers, and students as informants. The main findings of the study indicate that learning planning has been systematically arranged through teaching modules and the selection of visual designs that are appropriate to student characteristics. Learning is carried out effectively and interactively because Canva media is applied at all stages of learning. The use of the Canva application has been proven to significantly increase student interest in learning, as seen from the increase in student attention, interest, activeness, and enthusiasm in participating in the learning process. In conclusion, the active role of teachers in integrating Canva digital media has succeeded in creating a fun and interactive classroom atmosphere, while also being an effective solution to overcome boredom and boosting psychological engagement and active participation of students in Pancasila Education learning.